Science Technology Engineering Arts Mathematics (STEAM) Approach for Learning Science in Junior High School - Arum Kismawardani; Tukiran; Eko Hariyono (Studies in Learning and Teaching, 2022)
This study aims to determine how the application of the STEAM approach to science learning in junior high school. The research was conducted by giving questionnaires to science subject teachers at the junior high school level in Surabaya, Sidoarjo, and several surrounding areas. Based on the results of the questionnaire given to the science teacher, it showed that 72% of the STEAM approach had been understood by the science teacher, 12% said they did not understand the STEAM approach and the remaining 16% answered doubtfully whether they understood the STEAM approach in science learning. However, only about 50% of science teachers who understand carry out learning using the STEAM approach. As many as 28% stated the lack of supporting articles for implementing the STEAM approach. Another result stated that 56% of teachers had difficulty in referencing learning tools with the STEAM approach which had to be adapted to school conditions and another 16% needed training to apply the STEAM approach to be applied in learning. Based on the results obtained, the largest percentage needed by teachers to help implement science learning using the STEAM approach is the need for learning tools. Therefore, STEAM-based learning tools really need to be developed, especially for the science teaching and learning process.